2020
DOI: 10.1080/17436753.2019.1707412
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric examination of the optical effects of monolithic multilayered zirconia with different substrates

Abstract: The goal of this study is to examine specific optical effects of multilayered and coloured monolithic zirconia considering thickness and substrates of different colours using one of the most advanced spectrophotometers of the world. Multilayered zirconia specimens were used for the study with the thickness range of 0.5-2.5 mm and six types of substrate materials and three types of metal substrates. Measurements were carried out at Budapest Technical University with a PerkinElmer®Lambda1050UV/Vis/NIR spectropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
4
0
1
Order By: Relevance
“…18,20 Regarding the final appearance of monolithic zirconia restorations, studies emphasize the effect of abutment color, ceramic thickness, and their combined effect. 19,22,23 A research that compared the masking ability of monolithic zirconias and zirconiareinforced lithium-silicate glass ceramics with different layer thicknesses confirmed the influence of layer thickness and abutment color in addition to the better masking ability of monolithic zirconias. 24 Although PICN hybrid ceramics have been available on the market for 10 years, there is a lack of information regarding their masking ability.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…18,20 Regarding the final appearance of monolithic zirconia restorations, studies emphasize the effect of abutment color, ceramic thickness, and their combined effect. 19,22,23 A research that compared the masking ability of monolithic zirconias and zirconiareinforced lithium-silicate glass ceramics with different layer thicknesses confirmed the influence of layer thickness and abutment color in addition to the better masking ability of monolithic zirconias. 24 Although PICN hybrid ceramics have been available on the market for 10 years, there is a lack of information regarding their masking ability.…”
Section: Introductionmentioning
confidence: 88%
“…During the examination of lithium‐disilicate glass ceramics, it was found that the color of the abutment, the thickness of the ceramic and the color of the cement significantly influence the color of the restoration 18,20 . Regarding the final appearance of monolithic zirconia restorations, studies emphasize the effect of abutment color, ceramic thickness, and their combined effect 19,22,23 . A research that compared the masking ability of monolithic zirconias and zirconia‐reinforced lithium‐silicate glass ceramics with different layer thicknesses confirmed the influence of layer thickness and abutment color in addition to the better masking ability of monolithic zirconias 24 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Semmelweis Egyetem Fogpótlástani Klinikája 2013 óta vizsgálja a különböző kerámiák optikai tulajdonságait [1,2,7]. A vizsgálatok célja kimutatni, hogy a különböző színű csonkok hogyan befolyásolják a restau rá tum végleges színét a kerámia vastagsága és transz lu cenci á ja, valamint a ragasztócement optikai tulajdonságainak függvényében.…”
Section: Bevezetésunclassified